Components driving the detection of stunting cases among Posyandu cadres using precede model : A qualitative study in Sumedang district, Indonesia - Batubara, Astriana Marta; Februhartanty, Judhiastuty; Iswarawanti, Dwi Nastiti (Indonesian Nutrition Association, 2024)
Cadres of Posyandu are frequently considered the frontline of community health programs, including in detecting and managing stunting. However, there are limited descriptions of the relevant factors driving their roles in stunting detection, particularly based on the PRECEDE model. The purpose of this study was to describe the multifactorial components driving cadres in finding stunting cases in Sumedang District, West Java.